Robust cyst germination induction in Haematococcus pluvialis to enhance astaxanthin productivity in a semi-continuous outdoor culture system using power plant flue gas. (October 2021) - Cho, Seung Jun; Sung, Young Joon; Lee, Jeong Seop; Yu, Byung Sun; Sim, Sang Jun
Graphical abstract: Highlights: Germination was introduced into semi-continuous process for producing astaxanthin. 2.1-fold increase in astaxanthin productivity compared to the batch process. The semi-continuous process produced 700.4 mg L −1 of astaxanthin over 60 days. Semi-continuous astaxanthin production from industrial flue gas was demonstrated. Abstract: The microalgae Haematococcus pluvialis biologically converts CO2 into natural astaxanthin that possesses a strong antioxidant activity; its low carbon footprint and economic viability have allowed it to garner great attention. However, low efficiency of the cultivation process is a major hurdle in its commercial production. Here, additional nitrogen was provided to fully grown cells to induce efficient cyst germination, thereby rapidly increasing the number of cells containing astaxanthin. After germination, these cells were rapidly converted from zooids to cysts by nitrogen depletion, while maintaining a steady astaxanthin content of 5.5%. Consequently, a 2.1-fold increase in astaxanthin productivity in comparison with that in a batch culture was achieved. Moreover, the germination-based semi-continuous process yielded 2.6 times higher astaxanthin productivity in a large-scale culture using power plant flue gas and a polymeric photobioreactor. This study provides a promising cultivation strategy for the commercial mass production of natural astaxanthin.